Metabolic Characteristics in Obese Patients Complicated by Mild Thyroid Hormone Deficiency - Wang, X.; Liu, H.; Chen, J.; Huang, Y.; Li, L.; Rampersad, S.; Qu, S. (Hormone and Metabolic Research, 2016)
The prevalence of subclinical hypothyroidism (SH) is increasing, especially in obese people. The purpose of this study was to evaluate the difference in metabolic profiles between obese patients with mild increased thyrotropin (TSH) or with normal TSH. A total of 219 obese patients were recruited in this cross-sectional study. They were divided into 2 groups: obese patients with normal TSH (0.35–2.5 mU/l) and age-, and body mass index (BMI)-matched obese patients with higher-normal TSH (2.5–5.5 mU/l). We have named it compensatory hypothyroidism or mild thyroid hormone deficiency. Anthropometric data, glucose-lipid metabolism, markers of inflammation, body composition, and thyroid function parameters were measured. Results showed that: 1) The levels of fasting plasma glucose (FPG), high density lipoprotein cholesterol (HDL-C), and 25-hydroxyvitamin D levels were significantly lower in obese patients complicated by mild increased TSH than in obese patients with normal TSH (p<0.05). The fasting insulin (FINS) and C reactive protein (CRP) levels were significantly higher in obese patients complicated by mild increased TSH when compared to the obese patients with normal TSH (p<0.01). Jostel’s TSH index (TSHI) and standard TSH index (sTSHI) were significantly higher in obesity with mild increased TSH when compared to obesity with normal TSH (both p<0.001). Thyroid’s secretory capacity (GT) was significantly lower in obesity with mild increased TSH when compared to obesity with normal TSH (p<0.001). 2) In the obese patients complicated by mild increased TSH group, serum TSH was significantly positively correlated with ALT, AST and CP (p<0.05). In the obese patients with normal TSH group, serum TSH was significantly positively correlated with UA (p<0.05). In all subjects, serum TSH was significantly positively correlated with ALT, AST, FINS, CP, CRP, and UA (p<0.05), but negatively with DBP, FPG, and HDL-C (p<0.05). 3) There was significant difference of the prevalence of hyperinsulinemia and impaired fasting glucose (IFG) between the 2 groups (p<0.05). In Conclusion, obesity complicated by mild increased TSH manifested higher fasting insulin levels, more severe chronic low-grade inflammation, and lower HDL-C levels than obesity with normal TSH.
Keywords: thyrotropin; insulin resistance; obesity; metabolism